DO MUNICIPALITIES HAVE THE POWER TO REGULATE THE KEEPING OF “DANGEROUS” DOGS? - Hendrik J van As (Obiter, 2024)
Dog attacks and resultant deaths are frequent occurrences in South Africa. Pit bulls are responsible in many of these cases and there are calls for them to be banned. Dogs, however, are the property of their owners, and forcing people to give them up will amount to a deprivation of property and an infringement of a dog owner’s right to property, which is protected by section 25 of the Constitution. Dogfighting is rife in South Africa and the conduct of dog owners contributes to dogs being aggressive and leads to dog attacks. In terms of the Constitution, animal control is a functional area of concurrent national and provincial legislative competence; on a strict interpretation, this means that municipalities do not have the power to legislate on the function. However, everyone is guaranteed the right to freedom and security of the person, which includes the right to be free from all forms of violence from either public or private sources. As such, the municipality (as part of the State) must respect, protect, promote and fulfil the right. Municipalities also have a duty to promote a safe and healthy environment, and the power to make by-laws on matters they may administer. They may also exercise powers that are reasonable and incidental to the effective performance of municipal functions, which is supported by the principle of subsidiarity, the fulfilment of the duties arising from section 12 of the Constitution, and the objective to promote a safe and healthy environment. A municipality that has the necessary resources can legislate and enforce by-laws on matters listed in Schedule 4A and 5A of the Constitution, provided that such action seeks to further the objectives of Chapter 2 of the Constitution and is not in conflict with measures adopted by the national and provincial spheres. The National Society for the Prevention of Cruelty to Animals (NSPCA) is responsible for animal welfare, but the responsibilities of animal welfare organisations are becoming greater as urbanisation in South Africa accelerates and animals in many disadvantaged communities are in dire need of basic animal care. The suite of local government law is geared towards the social and economic upliftment of communities, and there is legislative justification for interventions by municipalities to address matters such as the control of public nuisances, dog licensing, the operation of pounds, and the conduct of community members that can alleviate the pressure on those organisations tasked with animal care. There are a number of legislative instruments that apply to animals. A consolidation of the provisions of the various pieces of legislation into a single by-law aimed at regulating the keeping and treatment of dogs, may result in increased law enforcement and (it is hoped) increased sentences as a result of amplified enforcement, as well as improved deterrence.